Vico’s Philosophical Understanding and his Philological Aporias. The Case of Western Marxism - Roldán, David A. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In this article the author analyzes the only significant reference that Marx made about Vico, in order to later present two of the principle interpretations of the Neapolitan’s thought by so called «Western Marxism». The objective is to bring to light the aporias that the said references are faced with, in order to reflect upon the tension between the historical-philological approach and the philosophical approach